Vulnerable communities in neoliberal India : perspectives from a feminist ethnographic approach - Mohan, Deepanshu; Chindaliya, Sakshi; Thomas, Ashika (New York : Routledge, 2025)
"Mohan, Chindaliya and Thomas offer an ethnographic critique of modern, neoliberal India from the perspective of studying the daily lives-livelihoods of marginalised, unsecured, informal vulnerable communities residing in the urban, peri-urban spaces across the nation. With case studies ranging from groups of: pastoralists, fisher-folk, and handicraft workers of Kashmir to the weavers of Kutch, and the factory workers and artisans of the Delhi capital, this edited volume of feminist ethnographies cover previously undocumented geographical and socio-cultural contexts of vulnerable groups, put together by the Centre for New Economics Studies, O.P. Jindal Global University. The diverse range of ethnographic case studies further explore the invisibilization of the growing informal sector in India's labor market, studied through the applied concepts of Gayatri Spivak's othering, Doreen Massey's power geometries and Pierre Bourdieu's (fractured) habitus. In addition to providing visual narratives of daily lifestyle, livelihoods of identified communities, our ethnographic analysis is rooted in discussing feminist paradigms from each study's respondents. A useful read for scholars and policymakers interested in understanding intersectional applications of development studies in context of the unsecured workforce in India, with application across disciplines of social-economic anthropology of South Asia, using the methodological lens of experimental ethnography"--
Nomadic narratives: Tracing the invisible trails of Bakarwal women -- Clay and struggle: The unlit kilns of Uttam Nagar Kumhars -- Fish on the footpath: The neglected Ga'ad Haenz of Kashmir -- Weaving livelihoods: The plight of Kutch's Hasta Kalakars -- Bordering informality: The woes of the Wazirpur Mazdoors -- Crafting identities: The fading artistry of Kashmiri papier maché -- Reflections.
Keywords: Ethnology -- India; Marginality, Social -- India; Women -- India -- Social conditions; Women's rights -- India -- History; Feminism -- India -- History; SOCIAL SCIENCE / Disasters & Disaster Relief; SOCIAL SCIENCE / Feminism & Feminist Theory